Penerapan Metode Hybrid AHP-TOPSIS Dalam Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik - Tsalatsatus Sa’adah; Herwis Gultom (CV. Multi Kreasi Media, 2026)
The selection of the best employees conducted manually and subjectively has the potential to cause calculation errors and unfairness in decision-making. Therefore, a system is needed to provide recommendations that are objective, fast, and accurate. This study aims to develop a web-based Decision Support System (DSS) for the process of selecting the best employees. The method used is a hybrid approach combining the Analytical Hierarchy Process (AHP) to determine criteria weights and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) to rank alternatives. The system was tested using actual case data to evaluate the effectiveness of the applied method. The results show that the employee named La Ode Raditya Sambaga achieved the highest preference value of 1.0000 and ranked first. Thus, the web-based hybrid AHP-TOPSIS decision support system is proven to assist management in making decisions more objectively, quickly, and accurately in selecting the best employees.